2022
DOI: 10.1002/cbdv.202100876
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of the Pearl Extract from Pinctada fucata martensii Dunker on UV‐Induced Photoaging in Mice

Abstract: Although the effect of pearl powder has been recognized for more than a thousand years from healthcare to beauty care, there has yet to be an in‐depth understanding of its anti‐photoaging effect. In the present study, the protective effect of pearl extract (PE) on UV‐induced photoaging in mice was evaluated. First, the amino acid analysis of PE was carried out. Then, different dosages of pearl extract gel (PEG) were applied topically on the shaved dorsal skins regions of mice before UV irradiation. Skin physio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 54 publications
(101 reference statements)
0
3
0
Order By: Relevance
“…After one week of adaptation, the mice were randomly divided into the following groups: control, model (UV radiation), low dose treatment (UV radiation + 150 mg/kg purslane extract), medium dose treatment (UV radiation + 300 mg/kg purslane extract), high dose treatment (UV radiation + 600 mg/kg purslane extract), and positive treatment (UV radiation + 100 mg/kg Vitamin E); 8 mice were allocated to each group [ 32 ]. A UV-induced skin injury model was established using a UV light box.…”
Section: Methodsmentioning
confidence: 99%
“…After one week of adaptation, the mice were randomly divided into the following groups: control, model (UV radiation), low dose treatment (UV radiation + 150 mg/kg purslane extract), medium dose treatment (UV radiation + 300 mg/kg purslane extract), high dose treatment (UV radiation + 600 mg/kg purslane extract), and positive treatment (UV radiation + 100 mg/kg Vitamin E); 8 mice were allocated to each group [ 32 ]. A UV-induced skin injury model was established using a UV light box.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, DPFRHY demonstrated notable anti-inflammatory and cell repair properties [39]. Furthermore, PEG exhibited the inhibition of IL-1β, IL-6, PGE, TNF-α, and COX-2 production while also providing enhanced protection against UV-induced photoaging in mice [40]. The polypeptide (SEP) extracted from by-products of bonito fish can significantly reduce the expression levels of IL-6, IL-10, and TNF-α and has a good anti-inflammatory effect [72].…”
Section: Peptide Anti-skin-photoaging Via Anti-inflammationmentioning
confidence: 99%
“…Research has demonstrated that marine bioactive peptides play a significant role in numerous anti-photoaging hypotheses [20], encompassing the oxidative stress theory [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37], the inflammatory response theory [38][39][40], the matrix metalloproteinase abnormal expression theory [41][42][43][44][45], the hyaluronidase abnormal expression theory [46][47][48][49][50], the elastase abnormal expression theory [47,51,52], and the melanin over-synthesis theory [53][54][55][56][57] (Figure 1). Based on this premise, the present study critically examines the anti-photo-aging properties of marine bioactive peptides, encompassing their molecular characterization and underlying mechanisms associated with photoaging.…”
Section: Introductionmentioning
confidence: 99%